Algaenan structure in the microalga Nannochloropsis oculata characterized from stepwise pyrolysis. (February 2017) - Zhang, Zhirong; Volkman, John K.
Highlights: Stepwise pyrolysis of the eustigmatophyte Nannochloropsis oculata carried out. Range of biomarkers and lipid and protein degradation products identified. n -Alkane/ n -alkene pairs, n -alkan-2-ones and C29 –C33 mid-chain ketones identified. Core of the algaenan is built from interlinked C32 1, 17-alkyl diols. Stepwise pyrolysis can be used for rapid screening for novel biomarkers in algae. Abstract: Dried biomass of the eustigmatophyte Nannochloropsis oculata was subjected to stepwise pyrolysis at 50 °C intervals from 310 to 610 °C to test the potential of the technique for investigating the algaenan structure of N. oculata and for determining a broad suite of biochemical constituents. Pyrolysis at 310 °C yielded mainly free lipids such as phytol, cholesterol, C32 alkyl diols, hexadecanamide and large amounts of phytol-derived alkenes from thermal desorption. Indole generated from protein degradation first appeared at 360 °C, indicating the onset of biopolymer breakdown. The pyrolyzate of 410 °C showed a simpler composition, dominated by 2-methyl-1H-indole and indole, and accompanied by low amounts of phenol and hexadecanamide. At 460 °C, algaenan breakdown was evident from the detection of C15 –C19 n -alkan-2-ones with a strong predominance of C17, and of C29 –C33 mid-chain ketones composed of a remarkable predominance of the symmetrical ketone C31 n -alkan-16-one. Small amounts of the mono-unsaturated C31:1 mid-chain ketone and n -alkene/ n -alkane doublets were also present. The chromatograms suggest that the algaenan structure of N. oculata is composed of repeating, interlinked C32 n -alkan-1, 17-diols, whereas the free plus bound lipids were dominated by the C32 n -alkan-1, 15-diol. The pyrolyzate at 510 °C was dominated by a bimodal distribution of C8 –C32 n -alkene/ n -alkane doublets showing a maximum at n -C14:1 and n -C26, with lesser amounts of ketones. Such a wide chain length distribution implies that other aliphatic lipids, perhaps derived from the long chain n -alkenols, might also be involved in the algaenan structure. Major constituents of the 560 °C pyrolyzate were aromatic compounds, including toluene, phenol and indole, but absolute abundances were low. It is notable that high molecular weight compounds such as the n -alkene/ n -alkane doublets were no longer detected at 560 °C. The results show that stepwise pyrolysis provides simpler chromatograms than a single pyrolysis of a whole sample at 610 °C and so can be a useful tool for identifying algaenan structures and/or related compounds in ancient sediments and modern microalgae.